2013
DOI: 10.1371/journal.pone.0064781
|View full text |Cite
|
Sign up to set email alerts
|

An RNA Aptamer Provides a Novel Approach for the Induction of Apoptosis by Targeting the HPV16 E7 Oncoprotein

Abstract: BackgroundHuman papillomavirus 16 (HPV16) is a high-risk DNA tumour virus, which is a major causative agent of cervical cancer. Cellular transformation is associated with deregulated expression of the E6 and E7 oncogenes. E7 has been shown to bind a number of cellular proteins, including the cell cycle control protein pRb. In this study, RNA aptamers (small, single-stranded oligonucleotides selected for high-affinity binding) to HPV16 E7 were employed as molecular tools to further investigate these protein-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 65 publications
(83 reference statements)
1
34
0
Order By: Relevance
“…In an interesting study, Nicol et al selected an RNA aptamer, termed A2, with high affinity to HPV-16 E7 [125]. Transfection of this aptamer into HPV-16-transformed cells resulted in induction of apoptosis and consequent inhibition of cell proliferation.…”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In an interesting study, Nicol et al selected an RNA aptamer, termed A2, with high affinity to HPV-16 E7 [125]. Transfection of this aptamer into HPV-16-transformed cells resulted in induction of apoptosis and consequent inhibition of cell proliferation.…”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…Transfection of this aptamer into HPV-16-transformed cells resulted in induction of apoptosis and consequent inhibition of cell proliferation. In addition, the authors demonstrated that A2 bound to the N-terminal residues of E7 required for interaction with pRb and that, consequently, A2 disrupted the interaction between E7 and pRb in vitro [125]. Furthermore, the authors demonstrated that A2 enhanced E7 localization in the ER and that the A2-mediated reduction of E7 was not associated with proteasomal degradation suggesting that A2 perturbs normal E7 trafficking through promoting E7 ER retention [126].…”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…The single-stranded nature of RNA allows an RNA molecule to form a wide variety of secondary, tertiary, and even quaternary structures that enable a protein to not only interact with the ribonucleotide sequence, but also the nucleotide backbone in unique forms governed by the structure of the RNA. Indeed, RNA aptamers can be evolved in vitro that strongly interact with small molecules such as fluorophores 6 or specific proteins of interest 7,8 .…”
Section: What Is An Rna Binding Protein?mentioning
confidence: 99%
“…The same research group also isolated RNA aptamers against E7 oncoprotein that were able to disturb the E7-pRb interaction by targeting E7 for degradation and showed that one of them (A2) was able to inhibit cellular proliferation by inducing apoptosis in SiHa cervical carcinoma cells [54]. This effect was specific to HPV-16 transformed cells because it was not observed in HPV-free or HPV-18 cell lines [55]. Specific apoptosis induction of RNA aptamers targeting E6 and E7 oncoproteins suggests that these aptamers could have further applications in the future as therapeutic moieties.…”
Section: Aptamers Against Hpvmentioning
confidence: 99%